DISCLOSURE OF PRINCIPALS-AGENT BEHAVIOR DUE TO ASYMMETRIC INFORMATION BASED ON LOCAL VALUES IN INSTITUTIONS VILLAGE FUND MANAGEMENT: DISCLOSURE OF PRINCIPALS-AGENT BEHAVIOR DUE TO ASYMMETRIC INFORMATION BASED ON LOCAL VALUES IN INSTITUTIONS VILLAGE FUND MANAGEMENT - Subhan, Subhan Purwadinata; Ika Fitriani,; Asmini, Asmini (International Journal of Social Science, 2022)
The purpose of this study is to uncover the main agent behavioral problem caused by asymmetric information. The focus of this research is on identifying and answering behavioral issues that occur between principals and agents in the village fund management institutions. The methodology design uses an interpretive paradigm approach by applying a principals-agent theory based on information, that is, tracing the relationship of informant behavior in symbolic interactions that are interpreted by the cultural values of Sumbawa. Qualitative research and indepth interviews were conducted with several competent speakers on village fund management institutions and Sumbawa cultural experts. The research shows that there is asymmetric information about the use of village resources by agents who make themselves opportunistic and weaken the trust of the principals (village community) in him. The solution to the problem is a sabalong desa behavioral approach (improvement of the village) in the sense of mutual value and mutual trust in the value system of congratulations (towards security) and the value of justice and balance in the sabalong Samalewa value system uses relationships between village communities and village leaders institutionally. The conclusion of the study is that asymmetric information makes the agent behavior opportunistic and weakens the confidence of the principalss, through mutual value (mutual trust) and mutual worth (mutual respect), in the value system of the salamat (towards safety) and value be overcome by justice and the value of balance of values sabalong samalewa (balanced and harmonious) to strengthen the institutional management of village funds.